O trabalho do jornalista nos bastidores da televisão na era digital: O programa Cidade Alerta Paraíba. - Macêdo, Anne Kelly da Silva (2015)
The research investigates to what extent the work of the television journalist is influenced by the use of technologies, inside the work routine within the newsroom. To this end, we analyzed how the use of these new technologies has created tensions, conflicts, changes and transformations in the working area of the journalism team of the program Cidade Alerta Paraíba. The choice of this program as an object of study is justified by the fact that this TV program is one of the most relevant in Paraíba, also because it achieves the simplest population. We have adopted as a guiding for this study the participatory research, because it is characterized, as well as the action research, by the interaction among researchers and members of the investigated situations. The data collection technique is the observation of the environment studied and the interview with the members of the staff who works for the program; we had as research sample, journalists who work as general editor, producers, reporters and editors of text and image. Methodologically we formulated questionnaires, interviews and studied deeply the results, in order to understand the factors that influenced and shape the work of media professionals, and to what extent these factors contribute to minimize or modify the role of journalists in newsrooms. From a theoretical point of view considering the phenomenon of informatization, we rely on the concepts of interactive technologies, productive routines and collaborative journalism.